Effects of temperature and solvents on structure variation of Yunnan lignite in preheating stage of direct liquefaction. (1st March 2019) - Hou, Ranran; Bai, Zongqing; Hao, Pan; Dai, Xin; Xu, Junli; Zheng, Hongyan; Guo, Zhenxing; Kong, Lingxue; Bai, Jin; Li, Wen
Abstract: Preheating stage is of significance for direct coal liquefaction process, especially for the low-rank coals, with high reactivity and suitable for direct coal liquefaction. Properties of solvents used in preheating stage could greatly affect structure of coal and conversion of its oxygen-containing functional groups. In this work, the preheating process of one Chinese Yunnan lignite (YN lignite) was conducted in tetralin (THN) and 1-methylnaphthalene (1-MN) to figure out the interactions between YN lignite and nonpolar aromatic solvents. In-situ diffuse reflectance infrared Fourier transformation (DRIFT) technique coupled with curve-fitting analysis and ion-exchange titration analysis and solid-state 13 C NMR were used to investigate the structural changes of YN lignite when preheated in different solvents at different temperatures. Additionally, swelling ratio determination and density function theory (DFT) calculation were employed to evaluate the strength of interactions existing between YN lignite and THN or 1-MN. The results show that, the decrease of oxygen-containing functional groups and increase of aromaticity occur when YN lignite are preheated in THN and 1-MN, and these changes are intensified with temperature rising. Moreover, THN and 1-MN have different effects on variation of YN lignite, especially for phenolic hydroxyl groups, which are more likely to be decomposed in THN, while carboxyl groups break down more easily in 1-MN at 200–300 °C. DFT calculation and swelling ratio results show that stronger noncovalent interactions (OHπ hydrogen bonds in particular) between THN and YN lignite result in weaker OH bond in phenolic hydroxyl groups and subsequently decomposition of more phenolic hydroxyl groups compared to 1-MN.